CtBP1-Mediated Membrane Fission Contributes to Effective Recycling of Synaptic Vesicles - Ivanova, Daniela; Imig, Cordelia; Camacho, Marcial; Reinhold, Annika; Guhathakurta, Debarpan; Montenegro-Venegas, Carolina; Cousin, Michael A.; Gundelfinger, Eckart D.; Rosenmund, Christian; Cooper, Benjamin; Fejtova, Anna (Cell Reports, 2020)
Compensatory endocytosis of released synaptic vesicles (SVs) relies on coordinated signaling at the lipid-protein interface. Here, we address the synaptic function of C-terminal binding protein 1 (CtBP1), a ubiquitous regulator of gene expression and membrane trafficking in cultured hippocampal neurons. In the absence of CtBP1, synapses form in greater density and show changes in SV distribution and size. The increased basal neurotransmission and enhanced synaptic depression could be attributed to a higher vesicular release probability and a smaller fraction of release-competent SVs, respectively. Rescue experiments with specifically targeted constructs indicate that, while synaptogenesis and release probability are controlled by nuclear CtBP1, the efficient recycling of SVs relies on its synaptic expression. The ability of presynaptic CtBP1 to facilitate compensatory endocytosis depends on its membrane-fission activity and the activation of the lipid-metabolizing enzyme PLD1. Thus, CtBP1 regulates SV recycling by promoting a permissive lipid environment for compensatory endocytosis. Ivanova et al. demonstrate a dual role of CtBP1 in synaptic transmission. Nuclear CtBP1 restricts synaptogenesis and vesicular release probability, whereas presynaptic CtBP1 promotes compensatory endocytosis via activation of the lipid enzyme PLD1. Phosphorylation by Pak1 controls the redistribution of CtBP1 from active zones toward endocytic sites linking presynaptic exo- and endocytosis.
CRIS-Team Scopus Importer:2020-02-25
Keywords: Bassoon; compensatory endocytosis; CtBP1; exo-endocytosis coupling; membrane fission; Pak1; PLD1; presynapse; synaptic vesicle pools; synaptic vesicle recycling